Evaluating Pharmacologic Interventions in Multiple System Atrophy with Predominant Parkinsonism: A Case Report - Cheruvatta, Sai Keerthana Puthiyedath; Pattambi, Mohammed Ameen; Koppara, Muhammed Irfan; Simon, Priscilla; Rajagopalan, Nair Shreedharsini; Sabith, Abdul (Asian Journal of Biological and Life Sciences, 2024)
Multiple System Atrophy (MSA) is a rare, progressive neurological disorder, more common in men, with an incidence of 0.1-3.0 per 100,000, typically emerging in people aged 50 to 60. The cause remains unknown and its pathology is marked by glial cytoplasmic inclusions and degeneration of the striatum and olivopontocerebellar regions. Multiple System Atrophy (MSA) can include symptoms such as problems with blood pressure control, movement, balance and coordination. MSA is often classified into two main types: MSA-P, primarily affecting movement and causing Parkinson’s-like symptoms and MSA-C, primarily affecting balance and coordination. A 78-year-old man with an underactive thyroid gland experienced a decline in cognitive function, difficulty controlling bladder function and movement problems such as slowness, shaking and falls. MRI findings of brain atrophy, gliosis and reduced blood flow supported an MSA-P diagnosis. Levodopa and other Parkinson’s medications were ineffective, indicating MSA-P’s poor response to dopaminergic treatment. Diagnosis and Management: MSA-P often mimics Parkinson’s disease but progresses more rapidly, shows poor levodopa response and presents with unique MRI markers. Enhanced diagnostic criteria and tools are needed, especially early in the disease. Treatments may ease symptoms but do not alter disease progression. Given the complexity of MSA-P and its severe prognosis (average survival <10 years), multidisciplinary management is essential for symptom control and quality of life improvement.
Keywords: Levodopa; Multiple Systemic Atrophy; Neurodegeneration; Parkinsonian